2017
DOI: 10.1016/j.celrep.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Accumulation Drives Proteome-wide Alterations in Mouse Models of Alzheimer’s Disease-like Pathology

Abstract: SUMMARY Amyloid beta (Aβ) peptides impair multiple cellular pathways and play a causative role in Alzheimer’s disease (AD) pathology, but how the brain proteome is remodeled by this process is unknown. To identify protein networks associated with AD-like pathology, we performed global quantitative proteomic analysis in three mouse models at young and old ages. Our analysis revealed a robust increase in Apolipoprotein E (ApoE) levels in nearly all brain regions with increased Aβ levels. Taken together with prio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 77 publications
2
33
0
Order By: Relevance
“…In addition to the effects of HIV-1, we explored the impact of Aβ on the HBMEC-EV proteome in the context of HIV-1. It was reported that increased brain Aβ induced profound proteome remodeling in multiple cell types, altering brain molecular pathways in an Alzheimer's disease (AD) mouse model [24]. Another brain proteomic study using a different AD mouse model with amyloid and neurofibrillary tangle pathologies indicated age-dependent immune responses and synaptic dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effects of HIV-1, we explored the impact of Aβ on the HBMEC-EV proteome in the context of HIV-1. It was reported that increased brain Aβ induced profound proteome remodeling in multiple cell types, altering brain molecular pathways in an Alzheimer's disease (AD) mouse model [24]. Another brain proteomic study using a different AD mouse model with amyloid and neurofibrillary tangle pathologies indicated age-dependent immune responses and synaptic dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this has been shown to be the case, as treatment of cultures with anti-C1q antibody inhibited microgliamediated synaptic elimination. In contrast, other proteomics studies failed to identify the enrichment of complement components in the hAPP mouse model and in AD patient post-mortem brain samples [200,201]. These contradictory data indicate that more studies should be conducted to fully clarify the role of the complement cascade in AD, aiming at distinguishing whether the progressive C1q accumulation at synapses, found by Dejanovic et al [199], is a sole consequence of the disorder or is also affected by the aging process.…”
Section: Overheating the Developmental Engine In Ad: When Complement-mentioning
confidence: 97%
“…There is also increased appreciation that better mouse models are needed to identify targets for therapeutic intervention in neurodegenerative diseases, including AD (Drummond and Wisniewski, 2017). The comprehensive proteome dynamics provided insights that enable the direct comparison of multiple different mouse models (Savas et al, 2017). Comparing the over-expressing hAPP transgenic model (TgCRND8) at early and late stages of the disease indicated large yet discordant effects on protein turnover.…”
Section: Discussionmentioning
confidence: 99%